PENGEMBANGAN ONTOLOGI TUJUAN WISATA BALI DENGAN PENDEKATAN KULKUL KNOWLEDGE FRAMEWORK - Cokorda Pramartha (LPPM STMIK STIKOM Indonesia, 2020)
Bali is one of the small islands in Indonesia that known as an international and national tourists destination. Many of Information related to tourist destinations in Bali is scattered and fragmented available on the Internet. This causes many of the potential tourists who want to find information related to tourist destinations in Bali to have to visit one site to another to aggregate the information. Besides, much of the information available on the Internet is human-readable but not for computer applications, and this becomes a challenge for computer applications to aggregate existing information. This study aims to develop an ontology model in the domain of Bali's tourism destinations by adopting the kulkul knowledge framework (Tri Hita Karana and Kala Patra Village) in which this ontology as a backbone of the semantic web can be utilised by computer-based applications to manipulate existing information for user needs. In this study, initial testing is done regarding the proposed ontological model by providing a set of questions that are commonly used by users when accessing information about tourism destination. So, it is expected that the propose ontology model will be able to provide information on tourism in Bali systematically.